Financialisation and structural change in Portugal: A Euro-resource-curse? - Mamede, R.P. (Financialisation in the European Periphery, 2020)
This chapter discusses the relation between structural change and financialisation in the Portuguese economy since the mid-1990s. In particular, it looks at the effects of the non-financial private sector’s indebtedness on the country’s productive structure, and how this relates to the economic crisis that hit Portugal after 2010. The chapter discusses the literature on Dutch disease and the way it can contribute to the understanding of the links between financialisation and structural change in the Portuguese economy. The increase in the value-added share of the non-tradable sector was a pervasive feature across the European Union (with the notable exception of Germany). The chapter also discusses the dynamics of international trade and the patterns of credit allocation. In sum, in order to understand the patterns of structural change in Portugal after 1995 one needs to consider the combined effects of high capital inflows, financial deregulation and external competitive shocks in the context of Portugal’s participation in the euro area.